2001
DOI: 10.1046/j.1440-1819.2001.00854.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin therapy for REM sleep behavior disorder

Abstract: Rapid eye movement sleep behavior disorder (RBD) is a parasomnia with clinical symptoms that include punching, kicking, yelling and leaping out of bed in sleep. Polysomnographic (PSG) finding showed REM sleep without muscle atonia. Clonazepam is generally used for treating RBD symptoms but melatonin was reported to be effective so we reconfirmed the effect of melatonin on RBD patients in the present study. We used melatonin (3-9 mg/day) which could ameliorate problem sleep behaviors remarkably, as well as %ton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
95
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(103 citation statements)
references
References 3 publications
(10 reference statements)
2
95
1
3
Order By: Relevance
“…Accordingly, further prospective studies using well-defined measurement techniques are required. As an objective measurement of treatment efficacy, reduction in REM sleep without atonia (RWA) measured by polysomnography (PSG) was reported in previous melatonin studies 4,5 ; however, the results of our present study of ramelteon and a previous study of pramipexole indicate their efficacy in treating RBD may be independent of reduced RWA. 6,7 The RBD severity scale (RBDSS) represents a further objective measure of the severity of RBD using video-PSG; however, measurements of RBDSS differed in 60% of patients between nights 1 and 2 in the original report.…”
contrasting
confidence: 51%
“…Accordingly, further prospective studies using well-defined measurement techniques are required. As an objective measurement of treatment efficacy, reduction in REM sleep without atonia (RWA) measured by polysomnography (PSG) was reported in previous melatonin studies 4,5 ; however, the results of our present study of ramelteon and a previous study of pramipexole indicate their efficacy in treating RBD may be independent of reduced RWA. 6,7 The RBD severity scale (RBDSS) represents a further objective measure of the severity of RBD using video-PSG; however, measurements of RBDSS differed in 60% of patients between nights 1 and 2 in the original report.…”
contrasting
confidence: 51%
“…Long-term melatonin treatment is used to alleviate RBD symptoms (Takeuchi et al, 2001;Boeve et al, 2003;Kunz and Mahlberg, 2010). To chronically treat wild-type and transgenic mice, a melatonin (Sigma-Aldrich) solution was prepared in ethanol and dissolved in the drinking water (12.5 g/ml tap water, in 0.07% ethanol) for 2-4 weeks.…”
Section: Drug Preparation and Treatmentmentioning
confidence: 99%
“…Because the striatal dopamine circuit also regulates sleep quality (30), increased striatal L-dopa bioavailability by melatonin may modulate sleep in patients with PD. In terms of clinical studies, four reports of studies using polysomnography (PSG) have described that melatonin decreases RWA (6)(7)(8)(9). Furthermore, compared with clonazepam, melatonin may significantly lessen the risk of falls and injury in patients with PD (10).…”
Section: Discussionmentioning
confidence: 99%
“…To date, only one randomized controlled trial has reported beneficial effects of melatonin on RBD (6). Several open and retrospective trials (7)(8)(9)(10)(11) have also suggested that melatonin has beneficial effects on idiopathic and/or secondary RBD. Moreover, Nomura et al (12) reported that ramelteon was effective in treating patients with secondary RBD complicated by PD or MSA.…”
Section: Introductionmentioning
confidence: 99%